Variable Step Size P&O MPPT Algorithm on 250 W Interleaved Flyback Converter - Y. Munandar K.; Eka Firmansyah; Suharyanto Suharyanto (IJITEE (International Journal of Information Technology and Electrical Engineering), 2018)
Maximum power point tracking (MPPT) algorithm seek the MPP to maximize delivered the power of a photovoltaic panel. From several MPPT algorithms, the perturb and observe (P&O) algorithm is commonly used algorithm because of its easy implementation. However, it is not the most efficient algorithm due to the perturbation step is fixed. By using the high step size, the MPP tracking became fast but there would be a high steady state error and by using the low step size, there would be less steady state error but the MPP tracking became slow. Resulting in a waste of energy in steady-state conditions when the working point passes through the MPP and poorly dynamic performance indicated when the setpoint changes due to solar irradiation changes. In this paper, a modification variable step-size of the P&O algorithm has been proposed with setting the step-size automatically at each point of work. To validate the concept of modification variable step-size, simulation using PSIM has been carried out. Compared with the conventional P&O method with fixed step-size, the proposed modified P&O method can increase tracking speed and efficiency in the system.